Translation and validation of the German version of the Pet-Related Stress Scale - Hajek, André; Neumann, Ariana; Zwar, Larissa; Gyasi, Razak M.; Yon, Dong Keon; Pengpid, Supa; Peltzer, Karl; Corona, Rosalie; McDonald, Shelby Elaine; König, Hans-Helmut (Frontiers in Veterinary Science, 2025)
BackgroundPet-related stress refers to the stress of living with a pet. The aim of this study was to translate and validate the German version of the Pet-Related Stress Scale (PRSS-G). Moreover, reference values were determined.MethodsData for validation were gathered from a quota-based online sample of Germany’s adult population aged 18 to 74 years, with n = 3,270 representing the demographic distribution of Germany in terms of sex, age, and federal states. The data collection took place online in January 2025. Reliability was assessed, and confirmatory factor analysis was performed to evaluate construct validity. Concurrent validity was examined through pairwise correlations of PRSS-G with depressive symptoms, anxiety symptoms, perceived stress, life satisfaction and loneliness. Additionally, reference values were provided for key sociodemographic groups.ResultsStrong to excellent reliability was found for the PRSS-G, with Cronbach’s alpha of 0.96 overall and coefficients from 0.88 to 0.96 for the subscales. The mean pet-related stress score equaled 1.9 (SD: 0.8), with the highest levels among younger individuals, individuals with low education and individuals with a migration background. The original three-factor model (economic, psychological and social stress subscales) was confirmed in the present study. Higher pet-related stress was associated with more depressive symptoms (r = 0.50, p < 0.001), more anxiety symptoms (r = 0.48, p < 0.001), more perceived stress (r = 0.35, p < 0.001), lower life satisfaction (r = −0.13, p < 0.001) and higher loneliness (r = 0.30, p < 0.001).ConclusionThe PRSS-G is a reliable and valid tool to measure pet-related stress levels among individuals speaking German. To facilitate comparisons across different countries, additional translation and validation studies are required.